The villainess turns the hourglass. 6 - SANSOBEE (Comics author) (Ize Press, 2025)
Lady Isys, once the soon-to-be crown princess, has joined hands with the kingdom of Croa to revolt against the empire. But just as it's time for the coup to begin, it's revealed that the Croan king was in cahoots with the crown prince all along! After years of careful planning and deliberation, it is finally time for Aria to exact revenge on those who've wronged her--and the sorry sight of Mielle on her knees awaiting execution has made it well worth the wait! But unfortunately for Mielle, her demise won't be swift...After all, the best things in life should be savored, right?